Perception of Personal Protective Equipment (PPE) Use and Its Barriers in Clinical Settings - Sharma, Anjali; Hussain, Aqsa; Gunjan, Gunjan; Gupta, Asmita; Bhati, Deepanshu; Kumari, Ishita; Bhadoriya, Manas; Bhati, Jai; Garg, Hemant Kumar; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Personal Protective Equipment (PPE) is essential for infection control and occupational safety in clinical environments. Despite its proven efficacy, compliance remains suboptimal due to various perceptual and systemic barriers. Objective: To assess the perception of PPE use and identify barriers among healthcare trainees and professionals in clinical settings. Methods: A cross-sectional study was conducted among 250 participants: 100 MBBS students/interns, 50 nursing students, and 100 nurses/technicians. A 15-item Likert-scale questionnaire was developed to evaluate perceptions and barriers. Data were analyzed using descriptive statistics, ANOVA, and thematic analysis for open-ended responses. Results: While 82% of participants acknowledged the importance of PPE, only 61% reported consistent usage. Major barriers included discomfort (68%), lack of availability (54%), and time constraints (47%). Statistically significant differences (p < 0.05) were observed between student and professional groups in perceived risk and compliance behavior. Conclusion: Although awareness of PPE is high, practical barriers hinder optimal usage. Targeted training, ergonomic improvements, and institutional support are essential to enhance compliance and reduce occupational risk.